Pengaruh Pemasaran Hijau Dan Pengetahuan Produk Terhadap Niat Beli Dengan Persepsi Harga Sebagai Variabel Mediasi Pada Motor Listrik Honda EM1 e: (Studi pada Generasi Z di Indonesia) - Wiratama, Aryasena Reyhan; Basalamah, Muhammad Ridwan; Efendi, Erfan (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine whether purchase intention can be influenced by green marketing and product knowledge while being mediated by price perception. The research method used is a quantitative approach. This study utilizes a cross-sectional method and Structural Equation Modelling (SEM) to test the proposed research model. Eighty Gen Z who live in Indonesia and have the intention to buy Honda Em1 e: are being used as a sample for this research. The hypothesis was tested using descriptive statistical analysis, instrument testing, structural model testing, and hypothesis testing using the SmartPLS 4. The result of this study indicates that green marketing has a positive and significant influence on price perception and purchase intention, product knowledge has a positive and significant influence on price perception and purchase intention, price perception has negative and insignificant influence on purchase intention, green marketing has negative and insignificant influence on purchase intention through price perception, and product knowledge has negative and insignificant influence on purchase intention through price perception. The study provides practical insight for marketing and product managers to utilize green marketing, product knowledge, and price perception to enhance the consumers’ purchase intention.  Keywords: Purchase Intention, Price Perception, Green Marketing, Product Knowledge, Electric Vehicle.